Strategi Pengembangan Produk Baru Sel Punca: Studi Kasus di PT Bifarma Adiluhung (Regenic) - Astana, Yoseph Novi; Nurjanah, Siti (STREAMING, 2024)
The development of health technology driving the development of regenerative medicine such as cell therapy faces many challenges including during clinical trials for Covid-19 patients. This research aims to analyze the stem cells’s product development concepts related to Resource-based view and Stage-gate model, including appropriate development to minimize failure, as well as analyzing development challenges. Qualitative data was obtained from literature, observation and in-depth interviews with informants from the industrial, hospital and regulatory sectors in a semi-structured pattern. Analysis using N-Vivo produced seven themes, including development concept, strategy to minimize failure, and the development’s challenges. It was found that QbD principles were followed, but trial failure still occurs resulted from the un-focus gate in the Stage-gate model perspective, less RND organizing and firm capability. Broad differentiation strategy supported by continuous innovation and costs focus are important in business sustainability to overcome challenges involving managing and organizing firm’s resources to create valuable, rare, inimitable, non-substitutable resources and capabilities.